Impact of land property rights on the informal development of urban villages in China: The case of Guangzhou - Yang, Jinkun; Ma, Haitao; Fu, Wenjie; He, Yuanrong (Frontiers in Environmental Science, 2023)
Informal development, as a unique phenomenon that has become widespread in China's urbanization process in recent years, has continued to attract the attention of both the government and academia. Existing studies focus on urban village redevelopment strategies,little research has been conducted on informal development in urban villages under land property approach. In particular, research needs to further explore what impact China's collective land property rights have had on informality in urban villages. The study finds that land property rights have an important impact on urbanization and property rights arrangements have an important impact on resource allocation efficiency. Due to the ambiguity of collective land property rights in China, informal development in urban villages is the result of the collective action of villagers, government, and enterprises under the stimulation of economic development. The interaction of the three parties has promoted the rapid development of informal housing in urban villages.